Tendencje w doskonaleniu kadr w procesie szkoleń pracowniczych w organizacjach międzynarodowych - Stosik, Aneta; Głowicki, Piotr (Human resource improving trends in international organizations, 2006)
The article covers issue of improvement of human resources in contemporary international organizations. It includes analyses of Polish training market research in the last few years. It also includes short definitions and descriptions of all main training forms. On the basis of analyses the authors shaped conclusions and prognoses about future of training market in international organizations in Poland. The cultural aspect of organization was described in the training processes. It was shown that cultural demand influence in organization is the main element of projecting the training system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 273-282